Isoflavones in the Rutaceae family: twenty selected representatives of the genera Citrus, Fortunella, Poncirus, Ruta and Severinia - Koblovská, Radka; Macková, Zuzana; Vítková, Michaela; Kokoska, Ladislav; Klejdus, Borivoj; Lapcík, Oldrich (Phytochemical analysis, 2008)
Enzyme-linked immunosorbent assays in combination with semi-preparative high-performance liquid chromatography (HPLC) and analytical HPLC with mass spectroscopy in the selective ion monitoring mode were used for the determination of selected isoflavones, daidzein, genistein, biochanin A and their homologues, in 20 representatives of the Rutaceae family. Species belonging to five genera were studied, namely Citrus, Fortunella, Poncirus, Ruta and Severinia. The enzyme immunoassays used were based on polyclonal antibodies raised against isoflavonoid conjugates with bovine serum albumin (BSA), namely biochanin A-7-BSA, daidzein-7-BSA, daidzein-4'-BSA, genistein-7-BSA and genistein-4'-BSA. Aglycones as well as glycosides were detected, and methoxyisoflavones appeared to be more abundant than hydoxyisoflavones. The content of individual isoflavonoids ranged from 0 to 2.6 mg/kg (dry weight); the sum of all measured substances reached up to 5.9 mg.
Keywords: ELISA; Chromatography, High Pressure Liquid; Plant Components, Aerial; Rutaceae; isoflavony; Enzyme-Linked Immunosorbent Assay; nadzemní části rostlin; Isoflavones; vysokoúčinná kapalinová chromatografie